Asking the Right Questions: Screening Men for Partner Violence. Issue 15 (August 2022) - Velonis, Alisa; Maddox, Raglan; Buhariwala, Pearl; Kamalanathan, Janisha; Hassan, Maha Awaiz; Fadhil, Tamam; O'Campo, Patricia
With lifetime intimate partner violence (IPV) victimization rates for self-identified men between 14% and 20%, and an expanding understanding of gender as a nonbinary construct, practitioners in some clinical environments have expressed interest in screening all patients for IPV. Yet, few IPV screening instruments have been validated for use in nonfemale populations. This research tests the appropriateness and acceptability of a screening instrument developed for use with women. A literature review was completed to determine the current state of research into IPV screening practices tailored to men. Next, cognitive interviews were conducted to test a 9-question IPV screening instrument with men considered at average and elevated risk for experiencing partner violence. Participants were read the questions aloud and asked about item comprehension and question appropriateness and acceptability. The literature review uncovered no published reports describing routine clinic based IPV screening of men, and only two screening instruments had been validated with men. Twenty men participated in cognitive interviews from a variety of settings in a large urban center. All participants accurately described the intended meaning of each question and verified the appropriateness of asking the questions. This work addresses the gap in research on routine IPV screening with men, building on efforts to screen individuals and support improved health and response to violence to those across the gender spectrum.